The archaeofauna from iNkolimahashi Shelter, a Later Stone Age shelter in the Thukela Basin, KwaZulu-Natal, South Africa - Badenhorst, S. (Southern African Humanities, 2021)
The faunal sample from iNkolimahashi Shelter is large with an unusually high proportion of identifiable fragments. This is due to the large number of microfaunal remains, probably the result of burrowing rodents and owls nesting in the shelter. The rest of the sample, accumulated by humans, shows that small to medium-size bovids were hunted predominantly. The species composition is similar to that of other Later Stone Age sites in the Thukela Basin. A single sheep bone, grindstones and pottery suggest occupation of the shelter by agriculturists during the second half of the second millennium AD. To cite this article: Badenhorst, S. 2003. The archaeofauna from iNkolimahashi Shelter, a Later Stone Age shelter in the Thukela Basin, KwaZulu-Natal, South Africa. Southern African Humanities 15: 45-57.